Using the method of circuit training in the development of high speed and power abilities of 15-16-year-old basketball player - Pomeshchikova, I.; Chucha, N.; Shyriaeva, I. (Slobozhanskyi herald of science and sport, 2021)
Purpose: to determine the effectiveness of using a set of high-speed and power exercises by the circular training method in the training process of 15-16-year-old basketball players.